Three kinds of lucky - Harrison, Kim (Harrison, Kim, Shadow age, 2024)
"Petra Grady has known since adolescence that she has no talent for magic--and that's never going to change. But as a sweeper first-class, she's parlayed her rare ability to handle dross--the damaging, magical waste generated by her more talented kin's spellwork--into a decent life working at the mages' university. Except Grady's relatively predictable life is about to be upended. When the oblivious, sexy, and oh-so-out-of-reach Benedict Strom needs someone with her abilities for a research project studying dross and how to render it harmless, she's stuck working on his team--whether she wants to or not. Only Benedict doesn't understand the characteristics of dross like Grady does. After an unthinkable accident, she and Benedict are forced to go on the run to seek out the one person who might be able to help: an outcast exiled ten years ago for the crime of using dross to cast spells. Now Grady must decide whether to stick with the magical status quo or embrace her own hidden talents ... and risk shattering their entire world"--